2019
DOI: 10.1038/s41598-019-39929-1
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of Staphylococcus aureus cell wall teichoic acid is influenced by environmental conditions

Abstract: Wall teichoic acid (WTA) are major constituents of Staphylococcus aureus ( S . aureus ) cell envelopes with important roles in the bacteria’s physiology, resistance to antimicrobial molecules, host interaction, virulence and biofilm formation. They consist of ribitol phosphate repeat units in which the ribitol residue is substituted with D-alanine (D-Ala) and N-acetyl-D-glucosamine (GlcNAc). The complete S . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 53 publications
(67 reference statements)
3
58
0
Order By: Relevance
“…8A). The Wood 46 strain of S. aureus lacks protein A and is tarS ϩ /tarM Ϫ , leading to expression of ␤but not ␣-linked surface GlcNAc (37). Similar results were obtained with independent preparations of labeled bacteria.…”
Section: Receptors That Bind Gram-positive Staphylococcus Aureussupporting
confidence: 75%
“…8A). The Wood 46 strain of S. aureus lacks protein A and is tarS ϩ /tarM Ϫ , leading to expression of ␤but not ␣-linked surface GlcNAc (37). Similar results were obtained with independent preparations of labeled bacteria.…”
Section: Receptors That Bind Gram-positive Staphylococcus Aureussupporting
confidence: 75%
“…Of note, glycosylated WTA acts as bacteriophage receptors to mediate interspecies and intergeneric HGT and takes a great part in the pathogen-host immune response. Therefore, WTA has become an attractive drug target to the infection control of S. aureus and other Gram-positive pathogens in recent decades (Winstel et al, 2015;Mistretta et al, 2019;van Dalen et al, 2019). Gerlach et al demonstrated that tarP played a crucial role in the fitness of these lineages and raised concerns of further dissemination by horizontal gene transfer, but the role of this novel RboP-β-1,3-GlcNAc WTA epitope in immune response remained controversial.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput WTA structure analysis requires purified WTA specimens and nuclear magnetic resonance (NMR) spectroscopy, making the identification of WTA glycosylation patterns both time-consuming and laborious. The presence of the glycosyltransferase genes in S. aureus isolates which can be easily detected by PCR has been generally used to infer their WTA glycosylation patterns (Mistretta et al, 2019). Therefore, the investigation of WTA glycosyltransferase gene profiles may contribute to understanding the genetic diversification and the emergence of new pathogenic strains in S. aureus.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several possible changes to the cell wall have been observed in S. aureus during NaCl stress, such as shortened interpeptide bridges in the peptidoglycan (Vijaranakul et al, ), an increase in resistance to methicillin (Madiraju, Brunner, & Wilkinson, ) and increased autolysis activity (Ochiai, ; Stapleton et al, ). In addition to peptidoglycan, other components within the cell envelope, such as teichoic acids and more specifically their modifications with D‐alanine (Koprivnjak et al, ) and sugar residues (Kho & Meredith, ; Mistretta et al, ) are affected by osmotic stress. Combined, these findings indicate that the integrity of the cell wall is an important requirement for osmotic resistance.…”
Section: Introductionmentioning
confidence: 99%